Development of agricultural bionic mechanisms: Investigation of the effects of joint angle and pressure on the stability of goats moving on sloping lands - Zhang, Fu; Zheng, Limin; Wang, Wei; Wang, Yafei; Wang, Jiajia (International Journal of Agricultural and Biological Engineering, 2018)
The use of small-scale agricultural machinery becomes prevalent as it provides the stability of agricultural machinery research ideas. To lay the theoretical foundation for the research and design of agriculture walking mechanism, the Phantom Camera Control software was used to measure the anterior and posterior joint angle of a goat walking on different slopes. Foot pressure was measured by the film pressure sensor. The result of joint motion sequence, range of motion, and change of range showed that the fitting degree of the measured value was accurate. As the goat walking speed increased, the level of the hind limb angle changed to ensure itself stability. When the goat is walking, the forelimbs bear more weight than the hind limbs due to the different static and physiological structures of the front and rear legs. The key parameters of gait on different slopes were analyzed. The curve of angle change of legs was measured and analyzed when the goat is walking in slope. The results showed that, with the increase of the slope gradient, the anterior hip angle ranges from 83.3° to 117.1°, the posterior hip angle ranges at 120.3°-173.1°, the left knee angle ranges from 91.3° to 170.1°, the right knee angle is roughly the same as its range of variation. When the slope increased, the pressure change of left hind foot was consistent with that of the right anterior foot, and the pressure change of right hind foot was consistent with that of the left anterior foot. This demonstrated the theory of diagonal gait. Meanwhile, with the change of the slope, the plantar pressure of the limbs changes periodically. The research results verified the rationality of the four-legged bionic mechanism under various parameters, which can provide a theoretical basis for the design of agricultural walking mechanism to adapt different slopes in the hilly and mountainous areas. Keywords: bionic mechanisms, goat, slope, joint angle, pressure, stability DOI: 10.25165/j.ijabe.20181103.3633 Citation: Zhang F, Zheng L M, Wang W, Wang Y F, Wang J J. Development of agricultural bionic mechanisms: Investigation of the effects of joint angle and pressure on the stability of goats moving on sloping lands. Int J Agric & Biol Eng, 2018; 11(3): 35–41.